Strategi Pengembangan UKM Produsen Oleh-oleh Khas Malang (Suatu Tinjauan dari Lingkungan Bisnis, Inovasi, Knowledge Sharing Behavior dan Kinerja) - Rofiaty, Rofiaty (Jurnal Aplikasi Manajemen, 2011)
This research has a purpose to describe about business environment, Knowledge sharing behavior, innovation and performance at Small Medium Enterprise (SME's) that produce. This research involving manage 45 SME's as research samples, and using descriptive qualitative "oleh-oleh khas Malang" in Malang Raya-East Java. This research investigate about "How SME's can adapt to change with environment (their: competitors, customer behavior, regulation, etc), innovation, knowledge sharing behavior, and performance. Results of the research are: 1) raw material "soybean" sometimes there is a difficult to get it because must import from America, and for fruit chips faced scarcity because depend on the season of the fruits. 2) Knowledge sharing behavior at SME's through direct communication, but they always adaptive to change with customer taste to give customer satisfaction and to achieve sustainable competitive advantage on their industry. 3) Innovation showed from packaging and originally taste each fruits and SME's feels have high performance because they have loyality customer and high quality, by the way SME's products have delicious taste, unique taste and suitable with customer taste.